Stop Voicing and F0 Perturbation in Pahari - Nazia Rashid; Abdul Qadir Khan; Ayesha Sohail; Bilal Ahmed Abbasi (Acta Linguistica Asiatica, 2021)
The present study has been carried out to investigate the perturbation effect of the voicing of initial stops on the fundamental frequency (F0) of the following vowels in Pahari. Results show that F0 values are significantly higher following voiceless unaspirated stops than voiced stops. F0 contours indicate an initially falling pattern for vowel [a:] after voiced and voiceless unaspirated stops. A rising pattern after voiced stops and a falling pattern after voiceless unaspirated stops is observed after [i:] and [u:]. These results match Umeda (1981) who found that F0 of a vowel following voiceless stops starts high and drops sharply, but when the vowel follows a voiced stop, F0 starts at a relatively low frequency followed by a gradual rise. The present data show no statistically significant difference between the F0 values of vowels with different places of articulation. Place of articulation is thus the least influencing factor.